Prophecy And Reality: Hegemony In “1984” George Orwell And “Entrok” By Okky Mandasari - Tasya Putri Redina; Nurholis Nurholis (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This study investigates the hegemonic practices depicted in George Orwell’s “1984” and Okky Mandasari’s “Entrok,” comparing the methods of state control and indoctrination in both novels. Hegemony, as conceptualized by Gramsci, involves not just physical dominance but also ideological influence and societal consensus. This research employs a qualitative inductive method to explore how these novels represent state hegemony through their narratives and characters “1984” portrays a dystopian society where The Party exerts total control, influencing citizens from childhood through public spectacles and constant surveillance, leading to pervasive fear and compliance. Similarly, “Entrok” depicts the New Order era in Indonesia, where the state employs indoctrination intimidation to maintain power, affecting individuals and their communities. Through comparative literature theory, this study highlights the similarities and differences in the portrayal of state dominance in these two novels. The findings reveal that both novels illustrate the pervasive and multifaceted nature of hegemony, emphasizing the role of ideological control and the subtle mechanisms of power that shape societal behavior and beliefs.